Comparison of Effectiveness of Trunk PNF Versus NDT on Trunk Stability in Stroke Patients: Life Sciences-Physiotherapy - PT, Simi Hazarika; PT, Pallabi Goswami PT; Dutta, Abhijit; PT, Abhijit Kalita (International Journal of Life Science and Pharma Research, 2022)
Stroke is the commonest neurological deficit caused by an interruption of the blood flow to the brain and loss of trunk control is commonly observed in patients after stroke. Impaired trunk control has a negative impact on daily activities and quality of life(QOL) in patients after stroke. Proprioceptive Neuromuscular Facilitation (PNF) and Neurodevelopmental technique (NDT), both are effective in improving trunk control in hemiplegic patients by improving trunk muscle endurance, strength, and trunk mobility. This study is aimed to compare the effectiveness of trunk PNF and NDT to improve trunk stability in patients with stroke. The objective of the study was to compare the effectiveness of trunk proprioceptive neuromuscular facilitation and neuro-developmental therapy based on trunk protocol with conventional therapy to improve trunk stability in stroke patients 30 subjects who fulfilled the criteria were taken for the study and was categorised into 2 groups of A and B, each having 15 subjects. Group A received trunk proprioceptive neuromuscular facilitation along with conventional therapy & group B received neuro-developmental therapy based on trunk protocol along with conventional therapy respectively for 4 weeks. Before the study, all the subjects were assessed using a general assessment proforma. Both pre and post-treatment assessments were assessed by using trunk impairment scale and ROM of trunk flexion and extension. The results of statistical analysis were tabulated in terms of mean, standard deviation, variance, t-test, P-value, coefficient of variation in both groups. Paired t-test showed that there was a statistically significant improvement in both groups (P<0.05). The coefficient of variation is significant at the CV of group A (83.34) less than the CV of group B (100.16), therefore group A is more effective compared to group B. In this study, it was found that the trunk PNF technique with conventional exercises and NDT based on trunk protocol with conventional exercises was effective to improve trunk stability in acute or subacute stroke patients. But, the trunk PNF technique with conventional exercises was more effective than NDT based on the trunk protocol conventional exercises technique for improving the trunk stability in acute or sub acute stroke patients.